2020
DOI: 10.3917/rsi.142.0086
|View full text |Cite
|
Sign up to set email alerts
|

Recensement des thèses soutenues par les infirmiers en France à l’aube de la naissance de la discipline sciences infirmières

Abstract: L’année 2019 a officialisé la création de la discipline des sciences infirmières en France, dans la continuité du processus d’universitarisation amorcé depuis 2009. Si les infirmiers n’ont pas attendu cet acte de naissance pour s’engager dans un parcours doctoral, l’absence d’une filière universitaire en sciences infirmières n’a pas permis l’élaboration d’un état des lieux des thèses soutenues par des infirmiers dans les universités françaises. L’objectif de ce travail était de recenser ces travaux en identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…ND/NDS students enrol in different academic disciplines (education, sociology, psychology, public health and management). This population is fragmented between different academic disciplines, and similarly, there is no register of registered nurses (RNs) holding doctorates in France.Two previous studies reported a growing number of nurses undertaking doctoral studies in France; 26 doctoral students and 28 doctors were identified in 2009 (Jovic & Isambart, 2010) and 131 NDs since 1976 (Policard, 2020). We identified current ND/NDS through professional contacts of the principal investigator (PI) (NM) and RésiDoc listings (a ND/NDS association).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ND/NDS students enrol in different academic disciplines (education, sociology, psychology, public health and management). This population is fragmented between different academic disciplines, and similarly, there is no register of registered nurses (RNs) holding doctorates in France.Two previous studies reported a growing number of nurses undertaking doctoral studies in France; 26 doctoral students and 28 doctors were identified in 2009 (Jovic & Isambart, 2010) and 131 NDs since 1976 (Policard, 2020). We identified current ND/NDS through professional contacts of the principal investigator (PI) (NM) and RésiDoc listings (a ND/NDS association).…”
Section: Methodsmentioning
confidence: 99%
“…University recognition encourages more nurses to pursue academic training up to doctorate stages. Thus, in the absence of a university nursing curriculum, French nurses enrol in other scientific disciplines (Policard, 2020) to explore research themes linked to clinical and/or educational activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation